Influence of light quality on germination and initial growth of canephori seedlings Peltophorum dubium (Sprenge) Taub - Klein, Jeferson [UNESP]; Kestring, Debora [UNESP]; Schwantes, Daniel [UNESP]; Repke, Rodrigo A. [UNESP]; Mezzalira, Eder J. [UNESP]; Piva, Andre L. [UNESP]; Arrua, Miciades A. M. [UNESP]; Javorski, Cleovani R. [UNESP]; Rodrigues, Joao D. [UNESP]; Guimaraes, Vandeir F. [UNESP] (Wfl Publ, 2012)
Light is considered one of the major environmental factors controlling germination of different species, mainly native ones, based on the importance of the species Peltophorum dubium for re-vegetation of degraded areas, tree planting and landscaping. this study evaluated the germination and initial growth of canephori seedlings under light influence. Thus, the following treatments were adopted: T1-transparent germination box, T2-transparent germination box+transparent cellophane. T3-black germination box. T4-black germination box+transparent cellophane. T5-transparent germination box + blue cellophane and T6-transparent germination box+red cellophane. The evaluated characteristics were: germination percentage, germination velocity index (GVI), radicle, epicotyl, cotyledon and seedling length. dry matter, total chlorophyll and fractions a and b, and the ratio a/b. Seeds germinated in all treatments. However, higher biometric values were detected for seedlings subjected to lower light quality, i.e. in the dark, which stimulated etiolation. All evaluated pigments were influenced by light quality, and the lowest values were observed for plants from treatments presenting lower light quality.
Keywords: Germination; Light; Phytochrome; Re-vegetation